Development of Daily Meal Ordering System for Patient in Hospital using Web-Based Technology - Mohd Shuhaimi, Nur Aimisyazana; Mohamad, Mazita; Sudin, Noraisah (Evolution in Electrical and Electronic Engineering, 2022)
Food services carried out at most hospitals still use a paper menu than an electronic menu. Staff from the Department of Dietetics and Food Service need face-to-face interaction with the patient to take the order based on the doctor’s recommendation. The face-to-face interaction between hospital staff and patients could potentially spread the virus (COVID-19). To minimize the spread, a web-based meal ordering system was developed for patients and the Department of Dietetics and Food Service which also improves the hospital food service system. The users of this system are classified into two types, which are the patients and the administrator from the Department of Dietetics and Food Service. The system’s design was divided into two categories, namely the interface design (front-end) and database design (back-end). The design of t interface used the sublime text 3 as programmed, and XAMPP software which served as a web server. The Hypertext Markup Language (HTML) and PHP are the programming languages. For web development, MYSQL software was used in the database design. In terms of functionality, each interface has its requirements. The tests revealed that the interface and database were both successfully developed and functional. Patients can place their meals more efficiently with this approach. This approach also can be used to overcome the challenges and disadvantages that the Department of Dietetics and Food Service faces when using manual (paper) methods.